Update on Campylobacter vaccine development. Issue 6 (3rd June 2019) - Poly, Frédéric; Noll, Alexander J.; Riddle, Mark S.; Porter, Chad K.
ABSTRACT: Background : Acute diarrheal disease caused by viral, bacterial and parasitic infections are a major global health problem with substantial mortality and morbidity in children under five years of age in lower and middle income countries. However, a number of these infections also impact large segments of populations in upper income countries, as well as individuals who travel overseas for work, business or pleasure. Campylobacter has been and continues to be a leading cause of disease burden globally across all income countries. Aims : The aim of this review is to describe recent understanding in burden of disease, consider the current landscape of Campylobacter vaccine development, and address the challenges that need to be overcome. Sources : Relevant data from the literature as well as clinical trials described in European and US registries were used to conduct this review. Content : Despite advances in population health, food security, improved sanitation, water quality and the reduction of poverty, Campylobacter infections continue to plague global populations. The emerging recognition of chronic health consequences attributed to this pathogen is changing the potential valuation of preventive interventions. Advancing development of new vaccines is a present opportunity and holds promise.